2014
DOI: 10.1007/s11468-014-9749-5
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Refractive Index Sensor Based on D-Shaped Photonic Crystal Fiber with Rectangular Lattice and Nanoscale Gold Film

Abstract: We propose and investigate a D-shaped photonic fiber refractive index sensor with rectangular lattice based on surface plasmon resonance. In such sensor, the nanoscale gold metal film is deposited on the flat surface where it is side polished. Numerical results show that the average sensitivity of Au-metalized surface plasmon resonance (SPR) sensor could reach as high as 8,129 nm/refractive index unit (RIU) in the dynamic index range from 1.35 to 1.41 as well as 2,000 nm/RIU from 1.33 to 1.35. Compared to conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Dash and R. Jha [21] designed a sensitive D-shape PCF sensor based on SPR for near infrared region showing a spectral sensitivity of up to 5200 nm/RIU. Ming Tian et al [22] studied an all-solid D-shaped PCF-SPR sensor which showed a refractive index sensitivity of at least 7300 nm/RIU and An et al [23] described a high-sensitivity refractive index sensor based on the D-shaped PCF with a rectangular lattice exhibiting a spectral sensitivity of 8129 nm/RIU. It is obvious that the sensing performance of these sensors depends on the structures and in spite of recent advances, the average spectral sensitivity of D-shape sensors is still less than 10000 nm/RIU.…”
Section: Introductionmentioning
confidence: 99%
“…Dash and R. Jha [21] designed a sensitive D-shape PCF sensor based on SPR for near infrared region showing a spectral sensitivity of up to 5200 nm/RIU. Ming Tian et al [22] studied an all-solid D-shaped PCF-SPR sensor which showed a refractive index sensitivity of at least 7300 nm/RIU and An et al [23] described a high-sensitivity refractive index sensor based on the D-shaped PCF with a rectangular lattice exhibiting a spectral sensitivity of 8129 nm/RIU. It is obvious that the sensing performance of these sensors depends on the structures and in spite of recent advances, the average spectral sensitivity of D-shape sensors is still less than 10000 nm/RIU.…”
Section: Introductionmentioning
confidence: 99%
“…We assume the metal as gold, so ε ∞ = 5.9673 is the permittivity of the gold; ε = 1.09 can be interpreted as a weighting factor; ω is the angular frequency of guided L and L represent the frequency and the spectral width of the Lorentz oscillator; L /2π = 650.07THz; and L /2π = 104.86THz [18]. To decrease the energy loss, a perfectly matched layer and a scattering boundary condition are used in the calculation.…”
Section: The Structure and Basic Theorymentioning
confidence: 99%
“…The interaction between surface charge concussion and the optical Shuguang Li lishuguang@ise.neu.edu.cn 1 College of Information Science and Engineering, Northeastern University, Shenyang 110819, China electromagnetic field makes the surface plasmon have many unique and meaningful properties and have been applied in the area of chemistry, biology, environment and medicine, etc [5,25]. In SPR-based sensors, the famous KretschmannReather configuration is utilized [9].…”
Section: Introductionmentioning
confidence: 99%
“…For the SPR-based sensor, the sensitivity is already very high [1,8,22], but the detection range is often very narrow [14,26]. It is a disadvantage for biosensing applications especially the refractive index detection of various kinds of liquid in Chemistry.…”
Section: Introductionmentioning
confidence: 99%